Using the theory of planned behavior model to predict factors influencing breastfeeding behavior among preterm mothers at week 6 postpartum: the mediating effect of breastfeeding intention - Huang, Rong; Han, Hui; Ding, Lijing; Zhou, Yi; Hou, Yanwen; Yao, Xiao; Cai, Chenting; Li, Xiaohan; Song, Jianqi; Zhang, Shuying; Jiang, Hui (Frontiers in Psychology, 2023)
Background: Exclusive breastfeeding (EBF) in the first 6 weeks postpartum is key to continued breastfeeding. This study aimed to explore the role of EBF-related predictors (particularly breastfeeding intention) in breastfeeding behavior among preterm mothers at week 6 postpartum based on the theory of planned behavior (TPB).Methods: A total of 352 mothers of preterm infants were recruited, 340 of whom participated in this study. Prior to discharge, participants completed the Chinese versions of the modified Breastfeeding Attrition Predictive Tool, the Breastfeeding Knowledge Questionnaire (BKQ), the Infant Feeding Intention, and the Edinburgh Postnatal Depression Scale. Responses to the items of the BKQ were also collected by telephone at week 6 postpartum. The final analyses included 321 participants who completed the full two-wave data collection.The fitness indices of the modified TPB model were acceptable. Breastfeeding knowledge and EBF before discharge positively impacted breastfeeding intention, whereas depression had a negative impact. Breastfeeding intention fully mediated the impacts of breastfeeding attitude, social and professional support, knowledge, depression, and EBF before discharge on breastfeeding behavior, and partially mediated the influence of perceived breastfeeding control on breastfeeding behavior.These findings indicate that TPB accurately predicts breastfeeding behavior among preterm mothers at week 6 postpartum, and breastfeeding intention is key to the above-mentioned EBF-related factors and breastfeeding behavior. The findings underline the need for further longitudinal studies and corresponding interventions for the preterm mothers with high risk of EBF attrition.